2004
DOI: 10.1007/s00520-004-0687-1
|View full text |Cite
|
Sign up to set email alerts
|

Pain evaluation and management: a survey of Italian radiotherapists

Abstract: Results of the survey demonstrate that knowledge and attitudes of Italian radiotherapists towards the approach to and treatment of pain can be considered satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Saroyan et al [8] assessed pediatric pain knowledge among 3 residency training programs and found that anesthesiology residents had better knowledge compared to orthopedic or pediatric residents. The mean correct score of anesthesiology residents in the present study was not different from the study on radiotherapy residents done by Porzio et al [11] in 2005 (67.7% vs 63.7%). Although the questionnaire in their study had less number of items compared to the present study (16 items vs 35 items) and they had only 3 questions that specific to pediatric pain management.…”
Section: Discussioncontrasting
confidence: 76%
“…Saroyan et al [8] assessed pediatric pain knowledge among 3 residency training programs and found that anesthesiology residents had better knowledge compared to orthopedic or pediatric residents. The mean correct score of anesthesiology residents in the present study was not different from the study on radiotherapy residents done by Porzio et al [11] in 2005 (67.7% vs 63.7%). Although the questionnaire in their study had less number of items compared to the present study (16 items vs 35 items) and they had only 3 questions that specific to pediatric pain management.…”
Section: Discussioncontrasting
confidence: 76%
“…The consumption of opioids is at the lowest level among Western countries. In order to increase the use of opioids, a new law was promulgated and the knowledge and attitudes of Italian physicians involved in pain treatment were improved [10,11]. Nevertheless, consumption of opioids increased slowly, and this enhancement seems to be related principally to marketing strategies [4,8]; moreover, two recent works have demonstrated that patients in pain, observed during active treatment, receive inadequate therapy [2,5].…”
Section: Discussionmentioning
confidence: 97%
“…Otherwise pain is the main symptom bringing the large majority of patients to ask for medical intervention, and becoming, if uncontrolled, a very high cost of health in a country. Many systemic diseases can cause pain but many specialists (Porzio et al, 2005a(Porzio et al, , 2005bPeretti-Watel et al, 2003) who see these patients are not properly trained to recognize and to treat pain and suffering of their patients. A proper consultation with a pain specialist can markedly decrease the duration of a painful condition, and prevent higher pain sensations and "pain syndrome".…”
Section: Pain Is An Under-recognized and Under-treated Problemmentioning
confidence: 99%